2020
DOI: 10.1002/agj2.20005
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of adopting no‐till and cover crops in irrigated cotton production under risk

Abstract: Adoption of soil conservation practices has been promoted to improve environmental and economic benefits across the United States. These practices are especially necessary for soil health improvement in the Southern High Plains where soils are prone to erosion and agricultural irrigation relies heavily on groundwater. Winter cover crops and no‐till cropping are two conservation practices for reducing soil erosion, but producers might face additional risks associated with adopting these practices. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Similar observations were recorded in South Texas and West Tennessee, where risk-averse growers preferred no-tillage without cover crops over no-tillage with cover crops and conventional tillage (Boyer et al, 2018;Ribera et al, 2004). However, in the Texas High Plains under irrigated conditions, risk-averse growers preferred no-tillage with cover crops over no-tillage (Fan et al, 2020b).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Similar observations were recorded in South Texas and West Tennessee, where risk-averse growers preferred no-tillage without cover crops over no-tillage with cover crops and conventional tillage (Boyer et al, 2018;Ribera et al, 2004). However, in the Texas High Plains under irrigated conditions, risk-averse growers preferred no-tillage with cover crops over no-tillage (Fan et al, 2020b).…”
supporting
confidence: 74%
“…This can be attributed to significantly higher cotton yields (> 3,300 kg ha -1 ) under no-till cover cropping compared to other tillage types (1,100 -2,500 kg ha -1 ) in 2019 (Vulchi et al, 2023), followed by cost savings in tillage operations in the following years. Fan et al (2020b) observed similar results in Texas where no-till cover cropping systems produced greater or similar partial net returns compared to conventional systems, primarily due to higher yields under irrigated conditions. No significant differences in partial net returns were observed between cropping sequences and herbicide programs (LI and HI) averaged across other respective factors at College Station (Table 6).…”
Section: Partial Net Returns Analysis and Treatmentsupporting
confidence: 56%
“…Cover cropping has been promoted to provide multiple ecosystem services, such as soil health improvements, soil erosion control, and improved nutrient cycling (Frasier et al., 2016; Schipanski et al., 2014). However, their adoption rate has not advanced at the predicted pace because of the additional cost associated with seed purchase, planting, termination, and supplemental irrigation needed in arid and semiarid regions (Faé et al., 2009; Fan et al., 2020). One of the ways to offset cover cropping costs is to utilize cover crop biomass by harvesting forage or allowing cattle to graze.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the obvious importance of financial information in deciding whether to use alternative irrigation options (Adusumilli et al, 2016), there is less information about their profitability prospects under risk conditions. Moreover, in examining alternative farming practices, risk analysis utilizing SERF has been frequently used in recent years (Özkan et al, 2015;Liu et al, 2017;Adusumilli et al, 2020;Fan et al, 2020). The SERF technique ranks the preference of decision-makers (DMs) according to the value of the CE of each alternative.…”
Section: Literature Reviewmentioning
confidence: 99%